(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the role of philosophy in self-awareness, the main stages of the formation of philosophy, and the specific role of the philosophical worldview in the perception of the world are fully described.